Use of Isaiah in the fourth gospel in comparison to the Synoptics and other places in the New Testament - Rytel-Andrianik, P (2014)
Isaiah, along with Psalms and Zechariah, is one of the most quoted OT books in the Fourth Gospel (FG). There are thorough studies regarding the citations from Psalms and Zechariah in the FG. However, a monograph-length study on the use of Isaiah in that book is still lacking. The present research aims to fill this gap. This study proposes not only to research into Isaianic citations in the FG (Is 40:3; Is 54:13; Is 53:1; Is 6:9-10), but also to complete a comparative study of their other occurrences in the NT. This is done by analysing eleven citations in total, of which nine are found in the FG and Synoptics, while the other two are found in Acts and in the Letter to the Romans (one citation in each). This comparative study leads to the conclusion that the same citation, even with the same Vorlage, can be used with two different meanings in two different places in the NT. Indeed, even where similar meanings are to be inferred, the exact uses of the citations have some nuances. Moreover, the deviations in the form of the citations should not be understood simply as due to defective memory: they may be explained by “application of exegetical techniques and devices” (Menken) or they may not. It seems rather that the Fourth Evangelist crafted them well, according to his genuine theological aims/agenda. In fact, he is much freer in the composition of his citations than the Synoptics. In common with the Synoptics, however, he mentions Isaiah in order to gain prophetic authority for some difficult claims and not merely to indicate the source of the citation. Finally, it is observed that all of the Isaianic quotations in the FG have one pattern in common: where the OT writer refers to the God of Israel, the Fourth Evangelist refers to Jesus Christ.